2013
DOI: 10.3109/13880209.2013.810649
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 integrase activity ofMimusops elengileaf extracts

Abstract: The leaf extract from M. elengi had the strongest anti-HIV-1 IN activity with an IC₅₀ value of 62.1 µg/mL. A bioassay-guided isolation of the active compounds from M. elengi leaf extract resulted in the isolation of active compounds, identified as a mixture of gallocatechin and epigallocatechin. This mixture of gallocatechin and epigallocatechin showed satisfactory anti-HIV-1 IN activity with an IC₅₀ value of 35.0 µM. A flavanol glycoside, mearnsitrin was also isolated but was inactive at a concentration of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…In this regard, Sanguisorba officinalis [11] and Pelargonium sidoides [12] extracts inhibited the entry of the virus into the cells. Pometia pinnata [13] and Mimusops elengi [14] leaf extracts can modulate the activity of HIV integrase, and numerous vegetable extracts showed inhibitory potential on reverse transcriptase. [15] [16] In addition to crude extracts, essential oil (EO) isolated from aromatic plants by steam or hydro-distillation showed specific antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Sanguisorba officinalis [11] and Pelargonium sidoides [12] extracts inhibited the entry of the virus into the cells. Pometia pinnata [13] and Mimusops elengi [14] leaf extracts can modulate the activity of HIV integrase, and numerous vegetable extracts showed inhibitory potential on reverse transcriptase. [15] [16] In addition to crude extracts, essential oil (EO) isolated from aromatic plants by steam or hydro-distillation showed specific antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants with anti‐HIV‐1 activity have been studied intensively (Cheenpracha, Karalai, Ponglimanont, Subhadhirasakul, & Tewtrakul, ; Suedee, Tewtrakul, & Panichayupakaranant, ; Tewtrakul, Itharat, & Rattanasuwan, ; Wang et al., ). Ellagic acid is a naturally occurring polyphenol compound found in pomegranates, blackberries, raspberries, strawberries, and walnuts (Cerda, Tomas‐Barberan, & Espin, ; Vattem & Shetty, ).…”
Section: Introductionmentioning
confidence: 99%
“…Catechins isolated from green tea also had antiviral activity on influenza virus (Song et al, 2005) and epigallocatechin gallate was found to inhibit HIV-1 replication by blocking gp120-CD4 interaction (Nance et al, 2009). It has been reported that the mixture of gallocatechin and epigallocatechin isolated from Mimusops elengi leaf extract possess good anti-HIV-1 IN effect (Suedee et al, 2014). Protocatechuic acid has been shown to have antiinflammatory and analgesic properties in rats and mice (Lende et al, 2011).…”
mentioning
confidence: 99%